Shining light on recent advances in microbial mercury cycling - Daniel S. Grégoire; Alexandre J. Poulain (Canadian Science Publishing, 2018)
Mercury (Hg) is a global pollutant emitted primarily as gaseous Hg0 that is deposited in aquatic and terrestrial ecosystems following its oxidation to HgII. From that point, microbes play a key role in determining Hg's fate in the environment by participating in sequestration, oxidation, reduction, and methylation reactions. A wide diversity of chemotrophic and phototrophic microbes occupying oxic and anoxic habitats are known to participate directly in Hg cycling. Over the last few years, new findings have come to light that have greatly improved our mechanistic understanding of microbe-mediated Hg cycling pathways in the environment. In this review, we summarize recent advances in microbially mediated Hg cycling and take the opportunity to compare the relatively well-studied chemotrophic pathways to poorly understood phototrophic pathways. We present how the use of genomic and analytical tools can be used to understand Hg transformations and the physiological context of recently discovered cometabolic Hg transformations supported in anaerobes and phototrophs. Finally, we propose a conceptual framework that emphasizes the role that phototrophs play in environmental Hg redox cycling and the importance of better characterizing such pathways in the face of the environmental changes currently underway.